Case Report: Successful Chimeric Antigen Receptor T Cell Therapy in Haploidentical-Allogeneic Stem Cell Transplant Patients With Post-Transplant Lymphoproliferative Disorder - Yan, Nan; Wang, Na; Zhang, Peiling; Wang, Gaoxiang; Mao, Xia; Peng, Dan; Kuang, Dong; Chen, Liting; Zhu, Li; Zhou, Jianfeng; Zhang, Yicheng; Cao, Yang (Frontiers in Oncology, 2021)
Background Epstein–Barr virus-associated post-transplant lymphoproliferative disorder (EBV-PTLD) is a potentially fatal complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Rituximab has been proven to dramatically improve the prognosis of patients with EBV reactivation and PTLD. However, reports on the curative management of refractory PTLD are scarce. Case Presentation In this report, we describe the successful management of two patients with EBV-PTLD with chimeric antigen receptor T-cell (CAR-T) therapy. Conclusion The present results demonstrated that patients with EBV-PTLD may benefit from CAR-T therapy and that the toxicity is manageable. Further studies are needed to verify these findings.